Preparation of Mg3(OH)5Cl·4H2O Whisker with Brine - Zhu, Pinghua; Shi, Lipan; Deng, Haiyan (Asian Journal of Chemistry, 2013)
In this study, took brine as raw materials, researched the influence factor of water bath method preparing basic magnesium chloride whisker, concentration of magnesium chloride solution, the molar ratio of magnesium chloride and ammonia, the effect of ammonia feeding speed of and water bath temperature on the reaction. Analyzed the feature of basic magnesium chloride whisker through scanning electron microscope and analyzed and discussed the whisker growth mechanism and put forward the optimum technological conditions of preparing basic magnesium chloride whisker.